Improving access to affordable vaccines for middle-income countries in the african region. Issue 21 (9th May 2019) - Mihigo, Richard; Okeibunor, Joseph; Cernuschi, Tania; Petu, Amos; Satoulou, Alexis; Zawaira, Felicitas
Abstract: Despite the remarkable power of immunization reducing morbidity and mortality due to vaccine preventable diseases, one in five African children still does not receive all the basic, necessary vaccines. This is particularly true of the 10 middle-income countries (MICs) in the WHO African Region, where data demonstrates that immunization coverage is decreasing. These countries are not eligible for Gavi support in accessing new vaccines because of their relatively high per capita income level and will gradually increase with the transitioning of countries out of Gavi support. Thus, WHO was requested to facilitate access to affordable vaccines in relation to middle-income countries and those transitioning out of Gavi support in the near future. With commitment to address the issue, WHO Regional Office for Africa convened a consultative meeting from 09 to 11 April 2018 in Brazzaville, Congo to explore ways of improving access to affordable vaccines for MICs in the Region. The meeting brought together 17 low, middle and upper middle income countries in the African Region. Immunization partners and other WHO Regions also participated in the consultation to share experiences and explore ways of increasing access to affordable vaccines in MICs in the African Region. At the end of the meeting a number of solutions and action points were proposed for implementation in the Region.